PROPERTY MECHANICS AND PHYSICS OF CORAL AND CORAL FOUNDATION OF TRUONG SA ARCHIPELAGO - Luong, Hoang Xuan; Dat, Pham Tien; Chung, Nguyen Thai (Vietnam Journal of Marine Science and Technology, 2006)
PROPERTY MECHANICS AND PHYSICS OF CORAL AND CORAL FOUNDATION OF TRUONG SA ARCHIPELAGO